The Role of Risk Factors and Characteristic for Infantile Hemangioma at Wava Husada Hospital, Malang: Two Years of Retrospective Study - Ariani, Yuni; Aliyatur, T; Jatmiko, S W (Jurnal Plastik Rekonstruksi, 2022)
Introduction:. Infantile hemangioma is a prevalent tumor in children Method: This research is a case control study. The data from January 1, 2019 to December 31, 2021 were processed and presented to assess the incidence and percentage of risk factors for infantile hemangioma. Univariate, bivariate and multivariate analysis was performed using Microsoft Excel SPSS 21 spreadsheet program. Result : Total sample in this research is 201. The risk factor for mothers aged between 22-30 years to give birth to a child with infantile hemangioma is 4.257 times greater than that of mothers aged less than 22 years. The risk factor for mothers aged more than 30 years to give birth to a child with infantile hemangioma is 9.960 times greater than that of mothers aged less than 22 years. The risk factor for patients with a family history of hemangioma was 14.175 times greater than those without a family history of infantile hemangioma or vascular abnormalities. The risk factor of using preconception drugs during pregnancy had a 4.914 times risk than those who did not use preconception drugs during pregnancy. Conclusion: Infantile hemangioma is more common in women with average birth weight. Mothers aged 22-30 years are at greater risk of giving birth to a child with infantile hemangioma. Family history of infantile hemangioma carries a greater risk than those without. The use of medications during pregnancy is associated with a greater risk of infantile hemangioma than not.